Desenvolvimento e padronização de um método para determinação da sensibilidade do mycobacterium tuberculosis a fármacos contra tuberculose - Castellani, Luiz Guilherme Schimidt (2013)
Drug resistance has become a worldwide threat to tuberculosis control. Its early detection allows the doctor to use more appropriate treatment regimens and thereafter to break the transmission chain of the bacilli. Current drug susceptibility tests, though efficient, are expensive and/or lengthy and/or laborious. Based on that premise, we proposed to develop and standardize a direct phenotypic method to determinate the susceptibility of Mycobacterium tuberculosis to first line drugs used on tuberculosis treatment. To develop this new method, it was used the principles of the proportion method and the Ogawa-Kudoh swab culture method. The study was divided in two phases. The first was characterized by the development and standardization of the proposed method and the second by analyzing the agreement between the developed method and the MGIT method (gold standard). In the first phase, several assays were realized to define: the absorption and liberation volumes of liquids from different kinds of swab, the culture medium, the drugs concentrations and the time to read/interpret the cultures. Besides, it was verified if the sample should or should not be diluted. Based on results, the method was standardized with: commercial swab, Ogawa-Kudoh culture medium containing separately 0,2 μg/mL of isoniazid, 40,0 μg/mL of rifampicin, 10,0 μg/mL of streptomycin e 500,0 μg/mL of para-nitrobenzoic acid. It was also standardized that the sample should not be diluted and the cultures should be read/interpreted between 21 and 28 days. The comparative analyzes between this method and the susceptibility test on MGIT system indicated a kappa index equal to 1,000, which means a perfect agreement to gold standard. Given these promising results, we believe that the developed method presents a great potential to be used in laboratories with little infrastructure, because of its low cost, it is easy to perform and relatively fast.